SIMULATION FOOTBALL PLAYER HEALTH MONITORING USING IOT (INTERNET OF THINGS) and IMAGE PROCESSING - Ahmad Syaifudin; FikriHelmi Setiawan; Yopi Almarij; Muhammad Bima Pramadinata; Ari PurnoWahyu W (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In football game need requires excellent physical condition and a long playing pattern, football is a game that is very popular both young and old in this game the players are strictly selected from their physical condition and stamina, at the level of playing football will make movements like running and sprinting for the attack and the dodge process, this game pattern causes injuries to and sometimes becomes fatal. in the modern era players use tools for monitoring with the help of IOT (Internet of things) tools which are integrated with E-health system, this system is used to monitor temperature and heart rate from player temperature, IOT tools can be used during training and during matches, this method able to use as a recommendation for players to compete, this IoT system can be juxtaposed with image processing techniques where this image system can monitor the player's movement pattern so the player's condition able to read with the system, an additional algorithm that can record and recognize the player's name clearly so that the analysis process Movement data and body condition become accurate, the IOT method and image processing techniques able to carried out simultaneously so that if a system has problems it will be resolved with another system.